KUALITAS KEHIDUPAN KERJA, SELF EFFICACY, DAN KINERJA KARYAWAN: EFEK MEDIASI MOTIVASI KERJA (Study pada PT Bank BRI Cabang BSD) - Kusnoto, Kusnoto; Sitorus, Tigor (Jurnal Manajemen, 2016)
This research is driven by the phenomenon and the difference of research result about the correlation relationship between Quality Work of Life and Self efficacy with Employee Performance, therefore the researcher tries to fill the research gap by proposing Work Motivation as a mediating variable, where research with survey method conducted on 180 employees PT. Bank BRI Branch BSD. Analyze research by using model of structural equation with results; 1). Quality work of life has a significant negative effect on employee performance, 2). Quality work of life has a significant positive effect on work motivation, 3). Self efficacy has a significant positive effect on the performance of the karawan, 4). Self efficacy has a significant positive effect on work motivation, 5). Motivation of work has a significant positive effect on employee performance, so this finding proves that work motivation acts as a perfect mediator of Quality Work of Life with Employee Performance.Keywords: Quality of Work Life, Self efficacy, Motivation, Employee Performance